2012
DOI: 10.1016/j.jecp.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of self-regulation in preschoolers: Testing models of a field-based assessment for predicting early school readiness

Abstract: The importance of early self-regulatory skill has seen increased focus in the applied research literature, given the implications of these skills for early school success. A three-factor latent structure of self-regulation consisting of compliance, cool executive control, and hot executive control, was tested against alternative models, and retained as best fitting. Tests of model equivalence indicated the model held invariant across Head Start and private child care samples. Partial invariance was supported f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
83
2
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 76 publications
9
83
2
7
Order By: Relevance
“…Preschoolers already learn alongside and in collaboration with teachers and peers, and utilize their emotions to facilitate learning. Social emotional skills especially undergird their adaptation to the sometimes challenging preschool environment and subsequent successful schooling (Denham et al, 2011). Self-regulation becomes important for preschooler because it relates to mental health (Florez, 2011).…”
Section: Why Is Self-regulation Important For Preschooler?mentioning
confidence: 99%
“…Preschoolers already learn alongside and in collaboration with teachers and peers, and utilize their emotions to facilitate learning. Social emotional skills especially undergird their adaptation to the sometimes challenging preschool environment and subsequent successful schooling (Denham et al, 2011). Self-regulation becomes important for preschooler because it relates to mental health (Florez, 2011).…”
Section: Why Is Self-regulation Important For Preschooler?mentioning
confidence: 99%
“…Compliance and behavior regulation are considered important also in social interactions with teachers and peers (e.g., Denham, Warren-Khot, Bassett, Wyatt, & Perna, 2012;Eisenberg, Valiente, & Eggum, 2010). Previous studies have shown that poor regulation skills are associated with low levels of social competence in school-aged children (Denham et al, 2012;Eisenberg et al, 1995;Fabes et al, 1999) and high rates of externalizing problems in both children and adolescents (Eisenberg et al, 2000;Lengua, 2002).…”
Section: Development In the Classroommentioning
confidence: 99%
“…Previous studies have shown that poor regulation skills are associated with low levels of social competence in school-aged children (Denham et al, 2012;Eisenberg et al, 1995;Fabes et al, 1999) and high rates of externalizing problems in both children and adolescents (Eisenberg et al, 2000;Lengua, 2002). Different dimensions of regulation may have different antecedents and trajectories, as indicated by King's and colleagues ' (2013) findings that between 8 and 12 years of age, increases in effortful control but not impulsivity were associated with the level and rate of change in positive adjustment and adjustment problems.…”
Section: Development In the Classroommentioning
confidence: 99%
See 2 more Smart Citations